A contorted nanographene shelter - Huang Wu (Nature Portfolio, 2021)
Encapsulating large and contorted nanographenes inside artificial receptors remain challenging. This work reports the synthesis, characterization and binding properties of a trigonal prismatic cage compound that can serve as a receptor for contorted nanographene derivatives.